ERGONOMIC DESIGN OF PRAYER RUGS AND PROSTRATION (SUJUD) AIDS FOR ELDERLY AND DISABLED WORSHIPPERS: A MECHANICAL ENGINEERING APPROACH - Faisal Angriawan Malik; Haziq Idris; Lisa Larsson (Journal of Moeslim Research Technik, 2025)
Elderly and disabled Muslim worshippers often face significant physical challenges, particularly during the prostration (Sujud) phase of prayer, which can lead to pain, discomfort, and difficulty in performing religious obligations. Standard prayer equipment frequently fails to address these specific ergonomic needs. This study aimed to design, develop, and evaluate an ergonomic prayer rug and a mechanical prostration aid to reduce biomechanical stress and enhance comfort for this demographic. Employing a mechanical engineering design approach, the study involved anthropometric data analysis, biomechanical modeling of prayer movements, and Finite Element Analysis (FEA) for material stress simulation. Prototypes were fabricated and subsequently tested with a group of elderly and disabled participants. Data were collected using pressure mapping sensors and standardized comfort assessment surveys. The results demonstrated that the ergonomically designed rug, incorporating multi-density foam, significantly reduced peak pressure on the knees and forehead. The mechanical prostration aid effectively lowered the required muscular exertion and improved stability during the transition to and from Sujud. This research concludes that applying engineering principles to the design of prayer aids provides a viable solution for improving the safety, accessibility, and quality of religious practice for worshippers with physical limitations.